Importance–Performance Analysis of Bus Rapid Transit Service Attributes for Passenger Satisfaction and Sustainability - Putu Hermawati; Nadzirah Hj. Zainordin; Thung Wei Eng; A. A. Ayu Asta Oktaviani Putri; I Ketut Sutapa (Advance Sustainable Science Engineering and Technology, 2026)
The Bus Rapid Transit (BRT) system in Bali serves as a vital component of sustainable urban mobility. This study uniquely integrates Importance-Performance Analysis (IPA) with technical recommendations to provide a comprehensive evaluation of BRT performance and its contribution to sustainable transportation. The analysis identifies key service strengths—such as seating comfort, air conditioning, cleanliness, and personnel service quality—that exceed passenger expectations. Conversely, deficiencies are evident in bus stop conditions, accessibility for disabled passengers, punctuality, and environmental sustainability. By linking IPA results with actionable technical strategies, the study recommends upgrading bus stop infrastructure, enhancing accessibility design, implementing real-time scheduling, and tracking systems, transitioning to eco-friendly bus fleets, and strengthening passenger information and security systems. This integrated approach not only highlights priority areas for improvement but also offers a practical roadmap for policymakers and transit authorities to enhance service quality, boost ridership, and advance Bali’s progress toward a resilient and sustainable urban transport system.